(N|MPIRIOMONIZM (B:s (NsTATXI PO FILOSOFII (B/s - (NbOGDANOW(B, (NaLEKSANDR aLEKSANDROWI^s 1873-1928 ((NmOSKWA (B:s (NrESPUBLIKA(B,s, 2003)
(NkNIGA RASS^ITANA NA WSEH INTERESU@]IHSQ PROBLEMAMI FILOSOFII I ISTORII NAUKI(B.s
(NbIBLIOGR(B.: (NS(B. 386-388s
Keywords: (NfILOSOFIQ RUSSKAQs -- 19 - 20 (NWW(B.s; (NiSTORIQ FILOSOFII (B- (NrOSSIQ (B- 1895-1917s; (NrUSSKIJ MAHIZM I BOGOSTROITELXSTWO (B- (NsBORNIKIs; (NmETAFIZIKAs; (NoNTOLOGIQs; (NmONIZMs